(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The urgency of tackling agricultural adaptation is heightened by the significant trends in climate change currently visible, the probability of additional changes, and the growing magnitude of possible climatic effects more logically. There are many possibilities for adaption accessible for minor alterations to current agricultural systems, frequently; current climate risk management is modified. We demonstrate that putting these ideas into action is likely to affect some agricultural systems that will benefit from mild climate change. However, their efficacy is limited in situations that are more complex. Climate change is becoming more severe. As a result, additional systemic resource adjustments are required. Targeted diversification, for example, must be addressed when allocating resources of lives and production systems. We believe that obtaining increased adaptation activity will require climate change integration climate change-related problems with additional risk factors with other policy domains, such as variability and market risk, and other policy domains, such as long-term development. Dealing with the numerous obstacles to effective adaptation will require a multifaceted and dynamic approach.